Triticale as a Potential Trap Crop for the Wheat Stem Sawfly (Hymenoptera: Cephidae) in Winter Wheat - Peirce, Erika S.; Cockrell, Darren M.; Ode, Paul J.; Peairs, Frank B.; Nachappa, Punya (Frontiers in Agronomy, 2022)
Trap cropping involves the use of plant species or genotypes to attract pest insects away from the main crop to avoid pest damage. In this study, we evaluated the potential of using winter triticale (x Triticosecale) as a trap crop for the wheat stem sawfly (Cephus cinctus Norton), an economically devastating pest of wheat (Triticum aestivum L.). The wheat stem sawfly larvae consume parenchyma tissue within the wheat stem and cut the stem at the base causing it to lodge. Triticale is, on average taller and has a larger stem diameter than winter wheat. These traits are considered attractive to adult females when choosing hosts for oviposition. We conducted a two-year field study of one winter wheat and one winter triticale genotype combination for its potential as a trap crop. To complement the field study, we grew three genotypes of winter triticale and one winter wheat genotype in cone-tainers and infested them in the field. The cone-tainer and field studies revealed that the chosen winter triticale genotypes were not more attractive than the winter wheat genotypes for adult wheat stem sawflies. The field study also evaluated the average larval position in the stem and found the average position was variable between sampling dates in both crops. Thus, determining the precise timing of field swathing could destroy significant portions of larval populations. Future research should focus on genotype selection to establish triticale-wheat cultivar combinations to create a push-pull system.